Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the zeros of the polynomial function [tex]\( f(x) = x^3 + 6x^2 + 9x \)[/tex], we need to determine the values of [tex]\( x \)[/tex] for which [tex]\( f(x) = 0 \)[/tex].
Step-by-Step Solution:
1. Factor the polynomial:
The given polynomial is [tex]\( f(x) = x^3 + 6x^2 + 9x \)[/tex]. Notice that each term in the polynomial has a common factor of [tex]\( x \)[/tex].
2. Extract the common factor:
Factor out [tex]\( x \)[/tex] from each term:
[tex]\[ f(x) = x(x^2 + 6x + 9). \][/tex]
3. Factor the quadratic expression:
Next, we need to factor [tex]\( x^2 + 6x + 9 \)[/tex]. We notice that this quadratic expression is a perfect square trinomial:
[tex]\[ x^2 + 6x + 9 = (x + 3)^2. \][/tex]
4. Write the polynomial in its factored form:
Incorporating the factorization, the polynomial can be written as:
[tex]\[ f(x) = x(x + 3)^2. \][/tex]
5. Find the zeros of each factor:
Now, set each factor equal to zero and solve for [tex]\( x \)[/tex]:
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ x = 0 \quad \text{(This is one of the zeros)}. \][/tex]
- For [tex]\( (x + 3)^2 = 0 \)[/tex]:
[tex]\[ x + 3 = 0 \implies x = -3 \quad \text{(This is another zero)}. \][/tex]
6. List all the zeros:
The zeros of the polynomial function are:
[tex]\[ x = 0 \quad \text{and} \quad x = -3. \][/tex]
Therefore, the correct answer is [tex]\( \boxed{x = 0, x = -3} \)[/tex], which corresponds to option C.
Step-by-Step Solution:
1. Factor the polynomial:
The given polynomial is [tex]\( f(x) = x^3 + 6x^2 + 9x \)[/tex]. Notice that each term in the polynomial has a common factor of [tex]\( x \)[/tex].
2. Extract the common factor:
Factor out [tex]\( x \)[/tex] from each term:
[tex]\[ f(x) = x(x^2 + 6x + 9). \][/tex]
3. Factor the quadratic expression:
Next, we need to factor [tex]\( x^2 + 6x + 9 \)[/tex]. We notice that this quadratic expression is a perfect square trinomial:
[tex]\[ x^2 + 6x + 9 = (x + 3)^2. \][/tex]
4. Write the polynomial in its factored form:
Incorporating the factorization, the polynomial can be written as:
[tex]\[ f(x) = x(x + 3)^2. \][/tex]
5. Find the zeros of each factor:
Now, set each factor equal to zero and solve for [tex]\( x \)[/tex]:
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ x = 0 \quad \text{(This is one of the zeros)}. \][/tex]
- For [tex]\( (x + 3)^2 = 0 \)[/tex]:
[tex]\[ x + 3 = 0 \implies x = -3 \quad \text{(This is another zero)}. \][/tex]
6. List all the zeros:
The zeros of the polynomial function are:
[tex]\[ x = 0 \quad \text{and} \quad x = -3. \][/tex]
Therefore, the correct answer is [tex]\( \boxed{x = 0, x = -3} \)[/tex], which corresponds to option C.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.